Ida Fink idzie do szkoły - Krupa, Bartłomiej (Narracje o Zagładzie [czasopismo zamknięte], 2020)
In the text, the author takes a closer look at Ida Fink’s symbolic “return” to school. The writer, who had to abandon her studies in piano at the Lwów Conservatoire as a result of the Third Reich’s attack on the USSR in 1941, since the end of 1990s has been a frequent presence on Polish school curricula and exams. The essay analyses the very manner in which her works appear within the school canon, student’s books, as well as the Matura examination sheets. What is more, some of the rudimentary biographical mistakes and simplifications are reviewed in the text. Ida Fink’s case analysis also formed a basis for a wider glance at the evolution of the Shoah theme’s presence in Polish school.